Stochastic Resonance in a Multistable System Driven by Gaussian Noise - Peiming Shi; Pei Li; Shujun An; Dongying Han (Discrete Dynamics in Nature and Society)
Stochastic resonance (SR) is investigated in a multistable system driven by Gaussian white noise. Using adiabatic elimination theory and three-state theory, the signal-to-noise ratio (SNR) is derived. We find the effects of the noise intensity and the resonance system parameters b, c, and d on the SNR; the results show that SNR is a nonmonotonic function of the noise intensity; therefore, a multistable SR is found in this system, and the value of the peak changes with changing the system parameters.